Movements vary according to dispersal stage, group size, and rainfall: the case of the African lion. Issue 10 (1st October 2014) - Elliot, Nicholas B.; Cushman, Samuel A.; Loveridge, Andrew J.; Mtare, Godfrey; Macdonald, David W.
Abstract : Dispersal is one of the most important life‐history traits affecting species persistence and evolution and is increasingly relevant for conservation biology as ecosystems become more fragmented. However, movement during different dispersal stages has been difficult to study and remains poorly understood. We analyzed movement metrics and patterns of autocorrelation from GPS data for 20 lions ( Panthera leo ) over a five‐year period. We compared movement among different stages of natal dispersal (departure, transience, and settlement), in addition to that of territorial adults of both sexes. The movement of lions differed according to dispersal stage, sex, group size, and rainfall. As expected, during dispersal lions moved faster and further and in a more directional manner than pre‐ or post‐dispersal. Transient movement was more directional than adult movement, but somewhat surprisingly, was slower with less net displacement than that of territorial males. Interestingly, the effect of group size on movement differed between transient males and territorial males; solitary dispersers moved faster and further than individuals in bigger groups, while territorial males had the opposite trend. Although our sample size is limited, our results suggest a transition from directional movement during transience to random or periodic use of a fixed territory after settlement. In addition, group size may affect the search and settlement strategies of dispersers while seeking a territory in which to settle.